Influence of service ageing on polyester-reinforced polyvinyl chloride-coated fabrics reported through mathematical material models. Issue 8 (April 2019) - Zerdzicki, Krzysztof; Klosowski, Pawel; Woznica, Krzysztof
In this paper the coupled service (constructional tension) and environmental (sunlight, rainfalls, temperature variations) ageing influence on the polyester-reinforced polyvinyl chloride (PVC)-coated fabric VALMEX is studied. Two cases of the same fabric have been analyzed: one USED for 20 years on the real construction of the Forest Opera in Sopot (Poland), and one kept as a spare material (NOT USED). The following tests have been conducted: uniaxial tensile, biaxial tensile and long-term creep tests. The obtained results have been used for the parameter identification of the piecewise non-linear, Burgers and Bodner–Partom models. Next, the analysis of the influence of environmental conditions on the parameters of these models has been made. It has been concluded that some parameters are more and the others are less sensitive to the exposure to environmental and mechanical conditions. The change of material parameters for fill threads (due to larger deformation) is higher. The obtained results may be useful in the durability evaluation of the textile membranes reinforced with polyester threads and PVC coated. All the constitutive models with the identified parameters may be used for the numerical analysis of structures made of fabrics at the service beginning and after long-term usage.